Relapsing polychondritis: state-of-the-art review with three case presentations. Issue 8 (17th November 2021) - Grygiel-Górniak, Bogna; Tariq, Hamza; Mitchell, Jacob; Mohammed, Azad; Samborski, Włodzimierz
ABSTRACT: Background: Relapsing polychondritis (RPC) is a complex immune-mediated systemic disease affecting cartilaginous tissue and proteoglycan-rich organs. The most common and earliest clinical features are intermittent inflammation involving the auricular and nasal regions, although all cartilage types can be potentially affected. The life-threatening effects of rpc involve the tracheobronchial tree and cardiac connective components. Rpc is difficult to identify among other autoimmune comorbidities; diagnosis is usually delayed and based on nonspecific clinical symptoms with limited laboratory aid and investigations. Medications can vary, from steroids, immunosuppressants, and biologics, including anti-tnf alpha antagonist drugs. Method: Information on updated etiology, clinical symptoms, diagnosis, and treatment of rpc has been obtained via extensive research of electronic literature published between 1976 and 2019 using PubMed and medline databases. English was the language of use. Search inputs included 'relapsing polychondritis, ' 'polychondritis, ' 'relapsing polychondritis symptoms, ' and 'treatment of relapsing polychondritis.' Published articles in English that outlined and reported rpc's clinical manifestations and treatment ultimately met the inclusion criteria. Articles that failed to report the above and reported on other cartilaginous diseases met the exclusion criteria. Result: Utilizing an extensive overview of work undertaken in critical areas of RPC research, this review intends to further explore and educate the approach to this disease in all dimensions from pathophysiology, diagnosis, and management. Conclusion: RPC is a rare multi-systemic autoimmune disease and possibly fatal. The management remains empiric and is identified based on the severity of the disease per case. The optimal way to advance is to continue sharing data on RPC from reference centers; furthermore, clinical trials in randomized control groups must provide evidence-based treatment and management. Acquiring such information will refine the current knowledge of RPC, which will improve not only treatment but also diagnostic methods, including imaging and biological markers.